Transradial Versus Transfemoral Access for Percutaneous Coronary Intervention in ST-Segment–Elevation Myocardial Infarction: A Systematic Review and Meta-Analysis. (9th March 2021) - Di Santo, Pietro; Simard, Trevor; Wells, George A.; Jung, Richard G.; Ramirez, F. Daniel; Boland, Paul; Marbach, Jeffrey A.; Parlow, Simon; Kyeremanteng, Kwadwo; Coyle, Doug; Fergusson, Dean; Russo, Juan J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Transradial access (TRA) has emerged as the preferred vascular access site for coronary angiography and percutaneous coronary intervention. This systematic review and meta-analysis was performed to evaluate 30-day all-cause mortality comparing TRA with transfemoral access for percutaneous coronary intervention in patients with ST-segment–elevation myocardial infarction. Methods: We performed a systematic literature search and meta-analysis of randomized controlled studies published from inception until January 7, 2020, in MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science Core Collection. Preferred Reported Items for Systematic Reviews and Meta-Analyses guidelines were used for abstracting data. The primary outcome was all-cause mortality at 30 days. Secondary outcomes included myocardial infarction, major bleeding, stroke, and access site complications. Results: A total of 14 studies representing 11 707 patients (5802 patients with TRA; 5905 patients with transfemoral access) were included in this systematic review. All-cause mortality (N=8 studies) was significantly reduced in the TRA group with an overall risk ratio (RR) of 0.72 (95% CI, 0.56–0.92) in the pooled analysis. Major bleeding (N=12 studies; RR, 0.60 [95% CI, 0.45–0.80]) and access site complications (N=9 studies; RR, 0.40 [95% CI, 0.30–0.53]) were significantly higher in the transfemoral access group. There was no statistical difference in reinfarction (N=10 studies; RR, 0.96 [95% CI, 0.75–1.25]) or stroke (N=8 studies; RR, 1.47 [95% CI, 0.87–2.50]). Conclusions: TRA is associated with lower 30-day mortality, major bleeding, and access site complications when compared with transfemoral access in ST-segment–elevation myocardial infarction patients who undergo percutaneous coronary intervention. Registration: URL: https://www.crd.york.ac.uk/PROSPERO/ ; Unique identifier: 127955.